Real‐time functional magnetic resonance imaging neurofeedback can reduce striatal cue‐reactivity to alcohol stimuli. (10th June 2015) - Kirsch, Martina; Gruber, Isabella; Ruf, Matthias; Kiefer, Falk; Kirsch, Peter
Abstract: It has been shown that in alcoholic patients, alcohol‐related cues produce increased activation of reward‐related brain regions like the ventral striatum (VS), which has been proposed as neurobiological basis of craving. Modulating this activation might be a promising option in the treatment of alcohol addiction. One approach might be real‐time functional magnetic resonance imaging neurofeedback (rtfMRI NF). This study was set up to implement and evaluate a rtfMRI approach in a group of non‐addicted heavy social drinkers. Thirty‐eight heavy drinking students were assigned to a real feedback group (rFB, n = 13), a yoke feedback group (yFB, n = 13) and a passive control group (noFB, n = 12). After conducting a reward task as functional localizer to identify ventral striatal regions, the participants viewed alcohol cues during three NF training blocks in a 3 T MRI scanner. The rFB group received feedback from their own and the yFB from another participants' VS. The noFB group received no feedback. The rFB and the yFB groups were instructed to downregulate the displayed activation. Activation of the VS and prefrontal control regions was compared between the groups. We found significant downregulation of striatal regions specifically in the rFB group. While the rFB and the yFB groups showed significant activation of prefrontal regions during feedback, this activation was only correlated to the reduction of striatal activation in the rFB group. We conclude that rtfMRI NF is a suitable method to reduce striatal activation to alcohol cues. It might be a promising supplement to the treatment of alcoholic patients. Abstract : Increased activation of the ventral striatum (VS) to alcohol cues has been proposed as neurobiological basis of craving. We tested whether real‐time fMRI neurofeedback can modulate cue reactivity. Heavy drinkers were assigned to a real neurofedback group (rFB), a yoke neurofeedback group (yFB) and a passive control group. The rFB group received feedback from their own, the yFB from another participants VS. Both groups were instructed to downregulate the activation. We found VS downregulation specifically for rFB demonstrating the suitability of neurofeedback in alcoholism.